STUDENTS PERCEPTIONS OF THE IMPLEMENTATION OF PRACTICAL FIELD EXPERIENCE (PPL 2) AT SMK NEGERI 1 PALANGKA RAYA - Petrisly Perkasa; trissan, whendy; Ni Putu Diah Agustin Permanasuri; Trissan, Ardi Hosea (Jurusan Pendidikan Teknologi Dan Kejuruan, 2023)
PPL2 (Field Experience Practitioner) is a mandatory program that students at FKIP UPR must complete in orderto obtain some of the requirements to complete a bachelor's degree in higher education. This research wasconducted to find out the Perceptions of Students on the Implementation of Field Experience Practices (PPL 2) at SMK Negeri 1 Palangka Raya. This research is a correlational study (survey). The survey method is used toobtain data from certain natural (not artificial) places, but research does treatment in data collection, forexample by distributing questionnaires, tests, structured interviews and so on (non-experimental treatment).The population and samples taken were randomly 30 student respondents at SMK Negeri 1 Palangka Raya City.This study uses the validity test of the Product Moment correlation technique, which is to correlate the itemscores with the total score. Then, the data were analyzed using Pareto analysis in the form of a Pareto chart.Pareto diagrams in this study can show priority deviations and focus attention on the main issues that must beaddressed in efforts to improve. The result showed that students at SMK Negeri 1 Palangka Raya had a goodperception of the performance of UPR Teacher Training and Education Faculty students in carrying out FieldExperience Practice (PPL 2) as evidenced by the total answers of respondents on six indicators which includedpreparation of lesson plans, teaching processes, teaching skills, extracurriculars, relations with the school, andthe guidance process, namely students who have a good perception of 43.67%, quite good 23.56%, very good21.72%, not good 0.68%, and very not good at 0.57%